Audit Sistem Informasi Aplikasi Attendance Manager Menggunakan Framework Cobit 5 - Ruth Handayani; Eva Zuraidah (STMIK Budi Darma, 2024)
Framework Information system audits are carried out to identify and ensure that existing system procedures in the company function properly, using the Cobit 5 framework to audit the information system for the assistant manager application in the Clinic because previously there has never been a comprehensive audit of the information system used by the company so that the service The operation of the information system cannot be ascertained whether or not it meets the company's standard requirements and the only thing is that the machine is damaged suddenly, and if the attendce manager application is suddenly damaged then attendance is carried out manually on paper which results in the attendance being very long and ineffective. To see that remaining employee leave is not updated, an audit of the information system on the running Clinic Attendance Manager application is expected to be able to align needs with the company's goals, with quantitative capability analysis. The results of the audit with the two domains used, namely MEA01 Monitor, Evaluate and Assess Performance and Conformance, MEA02 Monitor, evaluate and assess the system of internal control, have not yet reached the expected target level. If sorted from the GAP closest to the target, it is MEA01.01 Establish a monitoring approach GAP value 0.97 MEA01.02 Set performance and conformance target value 0.77, MEA01.03 Collect and process performance and conformance data value 0.80, MEA01.04 Analyze and report performance value 0.53, MEA01.05 Ensure the implementation of corrective actions value 0.55, still far from the target, namely MEA02.01 Monitor internal controls with a value of -1.83, MEA02.02 Review business process controls effectiveness with a value of -1.35, MEA02.03 Perform control self-assessments with a value of -2.78, MEA02.04 Identify and report control deficiencies with a value of -1.70, MEA02.05 Ensure that assurance providers are independent and qualified with a value of -1.82.